2022
DOI: 10.1038/s41598-022-15677-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemometrics, health risk assessment and probable sources of soluble total petroleum hydrocarbons in atmospheric rainwater, Rivers State, Nigeria

Abstract: Total petroleum hydrocarbons (TPHs)—(aliphatic and aromatic) were analysed for in atmospheric rainwater between April–June; July–August; September–October depicting early, mid, late rain of 2019. Sampling at Rumuodomaya/Rumuodome and Ogale in Rivers State using basins fastened to a Table 2M above ground and 120 M from high features, Rainwater was analysed after treatment using Agilent GC-FID. Results show cumulative TPHs at R/R were 56.6551 mg/L, 39.5201 mg/L and 7.2283 mg/L, Ogale: 9.1217 mg/L, 59.4923 mg/L a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Wang et al 18 found that daily light rainfalls in the range of 1-20 mm play a crucial role in atmospheric particles' wet deposition rates. As reported in Omokpariola et al 19 , atmospheric rainwater directly affected PAH…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Wang et al 18 found that daily light rainfalls in the range of 1-20 mm play a crucial role in atmospheric particles' wet deposition rates. As reported in Omokpariola et al 19 , atmospheric rainwater directly affected PAH…”
supporting
confidence: 52%
“…As reported in Omokpariola et al . 19 , atmospheric rainwater directly affected PAH spatiotemporal variability and budget in heavily polluted areas in Nigeria. These findings indicate that precipitation can serve as a good marker of PAH sources, distribution, transformation and deposition pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Mazur et al [57] used GC-MS to identify pollutants in snow samples coming from several areas of Moscow city, and CA and Spearman correlation analysis [58] to evaluate the spatial distribution of pollutants. Omokpariola et al [59] used GC-FID to quantify the presence of hydrocarbons coming from petroleum processing in several samples of rainwater in Nigeria. The contamination found in that region is a serious problem, due to dermal and skin exposure, because rainwater is also a source of drinking water.…”
Section: Gas Chromatography (Gc) and Chemometricsmentioning
confidence: 99%
“…Chemical precursors of benzene such as benzoates and benzoic acid triggers hyperactivity in children, as other related health effect includes malaise (vomiting, headaches, body weakness, esophagus irritation), pseudo-allergy, urticarial and DNA changes [23,[46][47][48]. World health organization (WHO) review shows that sodium benzoate symptoms are relatively mild and fade-off within few hours but can be adverse health effect over prolong consumption of soft drinks [23,[47][48][49][50].…”
Section: Carcinogenic Risk Assessmentmentioning
confidence: 99%